(untitled) (Economic and Political Thought, 2017)
The article refers to the crisis of realism after the end of the cold war. It considers neoclassical realism as a promising theoretical attitude to revive the realist paradigm in the post cold-war bipolar international reality. The paper appreciates neoclassical realism’s return to a multifaceted concept of power present in Hans Morgenthau’s theoretical considerations and its acceptance of the importance of domestic variables developing the power of the state. Nevertheless, neoclassical realism is not a simple “return to Morgenthau”. It still emphasises the impact of systemic determinants and aspires more to a synthesis of classical and structural streams of realism. The article indicates that the idea of the synthesis contributes to some ambiguities in neoclassical realism’s assumptions, especially in the methodological context. Besides, neoclassical stream suffers some internal inconsistencies as a theoretical approach. Thus, neoclassical realism’s ability to revive realism in the post-cold war international relations is still disputable and the approach needs some more efforts to clarify and harmonize its theoretical assumptions.